Generation of sinapinic-acid containing extracts from irish rapeseed meal and characterisation of their bioactive properties for potential human health applications - QUINN, LEAH (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2020)
Rapeseed is one of the world’s major oilseeds, and Europe is the largest producer. During the extraction of the oil, a low economic- value by-product, rapeseed meal, is produced. Rapeseed meal is ordinarily used as an animal feed. It is rich in bioactive phenolics, including sinapinic acid, ferulic acid, caffeic and Ƥ-coumaric acid. Sinapinic acid has been shown to possess various bioactive properties including anti-diabetic, anti-inflammatory, anti-cancer and anti-oxidant activities. However, the amount of SA required to exert its beneficial effects exceeds what is obtainable from dietary intake alone. As such, the aim of this project was to isolate SA from a natural source, Irish rapeseed meal, to prepare extracts enriched with SA which could be consumed to prevent human disease. To achieve this aim, a survey of the literature was performed in order to determine a suitable extraction methodology, given previous studies have focused on the extraction of total phenolics, rather than SA alone. The rapeseed meal was first processed by freeze-drying to remove excess moisture before being defatted with hexane. The method by Naczk et al. 1992, which involves the use of a solvent mixture of methanol: acetone: water (7:7:6 v: v: v) was used to prepare a phenolic extract containing SA. The total phenolic content of the prepared extract was estimated using the Folin-Ciocalteu assay, while its SA content was determined using 1H-NMR spectroscopy. The yield of SA was determined to be 0.053 mg/mL of SA (5.3% w: v). As the yield of this extract was low in terms of dry weight and yield of SA content, the initial extraction methodology was modified. The key modification was the direct hydrolysis of the meal itself, rather than hydrolysis of the solvent extract. Sonication and centrifugation steps were also added to remove excess oil from the extract. This reduced the dry weight of the extract and as such the yield of SA was increased to 0.569 mg/mL of extract (57% w: v), as estimated by mass spectrometry analysis. The second aim of this work was to identify potential health benefits of the generated extracts, specifically heart health and anti- inflammatory activities using in-vitro and cell culture assays. The enzyme ACE-I (EC 3.4.15.1) plays a key role in hypertension and heart health. ACE-I is a zinc-dependent peptidase which cleaves angiotensin I (a vasodilatory peptide) to angiotensin II, which is a vasoconstrictor peptide involved in regulating blood pressure. A simple plasma ACE-I inhibition assay found that both extracts possessed ACE-I inhibitory activity, as did commercial SA. The toxicity of the extracts and commercial SA were assessed using physiologically relevant cell lines. Furthermore, the anti-diabetic potential of the extracts were also assessed. GLUT4 is a key regulator of insulin-dependent glucose uptake, and its dysfunction can lead to the development of type 2 diabetes. As GLUT4 has been shown to be epigenetically regulated, histone deacetylase inhibitor (HDACi) assays and Western Blot analysis was performed to determine the HDACi activity of SA. Our results found that commercial SA does not act as a HDACi. Polymerase chain reaction (PCR) and qPCR analysis revealed no effects on GLUT4 mRNA expression after both 24 and 48 hour treatments. A flow cytometry based fluorescent glucose uptake assay revealed the extracts inhibited glucose uptake, while commercial SA increased uptake in the H9c2 muscle cell line. Inflammation plays a key role in the pathology of various diseases including diabetes, cancer, arthritis and heart disease. Preventing or reducing chronic systemic inflammation could therefore provide symptomatic relief or prevent these ailments. Primary human peripheral blood mononuclear cells (PBMCs) were used as a cellular model which is more representative of the in-vivo setting. PBMCs were isolated from buffy coats, and treated with the extracts and commercial SA, followed by the addition of LPS. ELISA assays showed that both extracts and commercial SA significantly reduced the expression of the pro-inflammatory cytokines TNF-α, IL-12, IL- 6 and IL-1β. This project resulted in the: 1. Successful generation of extracts containing SA from Irish rapeseed meal using an efficient extraction procedure 2. Extracts which possess bioactivities relevant to human health 3. This approach may be suitable for valorisation of rapeseed meal for health benefits
APPROVED
Keywords: Rapeseed; Ireland; Rapeseed meal